The Identification of Key Online Learning Dispositions of College Students Learning in A Blended Learning Course (European Journal of Teaching and Education, 2020)
This paper discusses part of a practitioner research case-study which I carried out with a class of thirty-seven college students learning chemistry in a blended learning context. The full two-year study involved a multi-method interpretivist approach using observations, unsolicited meetings, VLE tracking system, students’ reflective journal, online informal discussions, questionnaires, focus groups and individual interviews. The study identified four key student online learning dispositions, i.e., the dispositions of resourcefulness, resilience, reciprocity and responsibility. These dispositions were identified as persona-related enablers for online learning and were found to be crucial for the students to develop a deep approach to learning. They were also instrumental for changes in the students as learners. These included changes in epistemological beliefs, study patterns, study habits and above all, changes in learner roles and learning identities. Notable changes occurred in a group of learners who were initially reluctant to learn from the online environment. This study showed that student learning dispositions may be transferred from one context to another. This includes a transfer of learning dispositions from the online environment to the face-to-face traditional classroom setting. Several educators argue that learning dispositions should be included as educational goals in educational curricula and should serve as practical strategies in creating learning environments. Learning activities should provide students with opportunities to develop and cultivate desirable dispositions for learning.